PRESENTATION OF LINGUOCULTUROLOGICAL PERSPECTIVES IN BERDAK WORKS (International conference on multidisciplinary science, 2024)
At the present time, several changes and developments in science are noticeable. At the same time, new branches and studies in Karakalpak linguistics began to be learned. If the study of the linguistic peculiarities of the Karakalpak folk works created linguistic folkloristics, then we must say that special studies are being conducted in the field of linguistic cultural (lingucultural) – on language units that radiates nationality in those folk works, customs and traditions in literary works. In this article, we decided to define the Karakalpak people's daily life, customs, traditions, and national culture of the Karakalpak people as their characteristics.